Implementing Best Practices and Validation of Cryopreservation Techniques for Microorganisms - David Smith; Matthew Ryan (The Scientific World Journal)
Authentic, well preserved living organisms are basic elements for research in the life sciences and biotechnology. They are grown and utilized in laboratories around the world and are key to many research programmes, industrial processes and training courses. They are vouchers for publications and must be available for confirmation of results, further study or reinvestigation when new technologies become available. These biological resources must be maintained without change in biological resource collections. In order to achieve best practice in the maintenance and provision of biological materials for industry, research and education the appropriate standards must be followed. Cryopreservation is often the best preservation method available to achieve these aims, allowing long term, stable storage of important microorganisms. To promulgate best practice the Organisation for Economic Development and Co-operation (OECD published the best practice guidelines for BRCs. The OECD best practice consolidated the efforts of the UK National Culture Collections, the European Common Access to Biological Resources and Information (CABRI) project consortium and the World Federation for Culture Collections. The paper discusses quality management options and reviews cryopreservation of fungi, describing how the reproducibility and quality of the technique is maintained in order to retain the full potential of fungi.